Absence of distal interphalangeal fold causing difficulty in extending fingers. Issue 6 (December 1977) - Lambert, D; Nivelon-Chevallier, A; Chapuis, J L
Abstract : A 13-year-old girl sought medical advice, saying that for two years it had been increasingly difficult for her to extend her little finger. An examination revealed that all her fingers, with the exception of her thumbs, had no interphalangeal fold. Her mother had less pronounced signs of the same type. This abnormality seemed to be the result of an autosomal gene with dominant transmission.